2014
DOI: 10.1177/1368430214523151
|View full text |Cite
|
Sign up to set email alerts
|

Which American way? System justification and ideological polarization concerning the “Ground Zero Mosque”

Abstract: The proposal to build an Islamic mosque and community center near the site of the terrorist attacks of September 11, 2001 on the World Trade Center produced widespread opposition. Although resistance among U.S. citizens was common, there was an ideological divergence, with liberals generally supporting the mosque and conservatives generally opposing it. We tested a theoretical model in which system justification mediated the effect of political ideology on level of support for the development of the "Ground Ze… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 16 publications
0
6
0
Order By: Relevance
“…The pro/anti-regime cleavage is also observed in contemporary Russia (Matovski, 2018) and Iran (Wojcieszak et al, 2019). Furthermore, Nam and Jost’s (2014) study demonstrated that mass ideological polarization is (at least partly) related to system-justification attitudes, which occur not only in authoritarian or semi-authoritarian contexts, but also in Western democracies such as the United States. By examining the American public’s opinions on the development of the Park51 mosque (also known as “Ground Zero Mosque”), Nam and Jost (2014) argued that ideological disparities on this issue are linked to system-justifying tendencies.…”
Section: Motive 1: the Out-group Exclusion Of Populismmentioning
confidence: 97%
See 2 more Smart Citations
“…The pro/anti-regime cleavage is also observed in contemporary Russia (Matovski, 2018) and Iran (Wojcieszak et al, 2019). Furthermore, Nam and Jost’s (2014) study demonstrated that mass ideological polarization is (at least partly) related to system-justification attitudes, which occur not only in authoritarian or semi-authoritarian contexts, but also in Western democracies such as the United States. By examining the American public’s opinions on the development of the Park51 mosque (also known as “Ground Zero Mosque”), Nam and Jost (2014) argued that ideological disparities on this issue are linked to system-justifying tendencies.…”
Section: Motive 1: the Out-group Exclusion Of Populismmentioning
confidence: 97%
“…Furthermore, Nam and Jost’s (2014) study demonstrated that mass ideological polarization is (at least partly) related to system-justification attitudes, which occur not only in authoritarian or semi-authoritarian contexts, but also in Western democracies such as the United States. By examining the American public’s opinions on the development of the Park51 mosque (also known as “Ground Zero Mosque”), Nam and Jost (2014) argued that ideological disparities on this issue are linked to system-justifying tendencies. According to their analysis, “to the extent that the development of the “Ground Zero Mosque” is experienced as a symbolic threat to the legitimacy and/or stability of the US system, system justification tendencies are likely to motivate opposition to the initiative” (Nam and Jost, 2014: 558).…”
Section: Motive 1: the Out-group Exclusion Of Populismmentioning
confidence: 97%
See 1 more Smart Citation
“…Thus, Westerners in regions traditionally dominated by Christian beliefs and Western customs, such as North America and Europe, may sometimes view Muslims and Middle-Eastern customs as a threat to their extant worldview (and vice versa). If so, this may help explain the culture clash between the West and the Middle East, reflected in the West via public rejections of Islam (Nam & Jost, 2014), anti-Islamic and anti-Arab prejudice (Kalkan, Layman, & Uslaner, 2009;Sniderman & Hagendoorn, 2007), aggression, and sometimes violence (Pyszczynski, Solomon, & Greenberg, 2003).…”
Section: Existential Threat and Anti-islamic Prejudicementioning
confidence: 99%
“…Building on studies documenting that conservatives possess chronically higher levels of system justification (e.g., Jost, Nosek, et al, 2008), Nam and Jost (2014) investigated the hypothesis that ideological differences in support for the development of the “Ground Zero Mosque” in New York City were (at least in part) a function of system-justifying tendencies. Consistent with this possibility, they observed that conservatives were more likely than liberals to oppose the development of the mosque (especially on behavioral, as opposed to attitudinal, measures) and that the difference was mediated by individual differences in system justification.…”
mentioning
confidence: 99%